X(x+4)-(x+4)=0 a(a-3)=2a-6

0 голосов
66 просмотров

X(x+4)-(x+4)=0
a(a-3)=2a-6


Математика (32 баллов) | 66 просмотров
Дан 1 ответ
0 голосов

X(x+4)-(x+4)=0
x²+4x-x-4=0
x²+3x-4=0
a=1, b=3, c=-4
D=b²-4ac=9-4*1*(-4)=9+16=25
x₁=\frac{-b+\sqrt{D} }{2a}= \frac{-3+5}{2} = \frac{2}{2}=1
x₂=\frac{-b- \sqrt{D} }{2a} = \frac{-3-5}{2}= \frac{-8}{2} = -4
Ответ: (1;-4)
a(a-3)=2a-6
a²-3a=2a-6
a²-3a-2a+6=0
a²-5a+6=0
a=1, b=-5, c=6
D=b²-4ac= 25-4*1*6=25-24=1
x₁=\frac{-b+ \sqrt{D} }{2a}= \frac{5+1}{2}= \frac{6}{2}= 3
x₂=\frac{-b- \sqrt{D} }{2a}= \frac{5-1}{2} = \frac{4}{2}=2
Ответ: (3;2)

(4.1k баллов)
0

cпасибо